"Goal-oriented adaptivity for linear elastic micromorphic continua based on primal and adjoint consistency analysis" - Ju, X.; Mahnken, R. (International Journal for Numerical Methods in Engineering)

"Model adaptivity on effective elastic properties coupled with adaptive FEM" - Ju, X.; Mahnken, R. (Computer Methods in Applied Mechanics and Engineering)

"Thermo-chemo-mechanical Effective Properties for Homogeneous and Heterogeneous n -Phase Mixtures with Application to Curing" - Dammann, Christian; Lenz, Peter; Mahnken, Rolf (Procedia CIRP)

(n)- AND (n + 1)-LAYERED COMPOSITE SPHERE MODELS FOR THERMO-CHEMO-MECHANICAL EFFECTIVE PROPERTIES - Mahnken, Rolf; Dammann, Christian; Lenz, Peter (International Journal for Multiscale Computational Engineering)

"Fuzzy and stochastic analysis of rubber like materials" - Penner, E.; Caylak, I.; Mahnken, R. (Proceedings of the 2nd International Conference on Uncertainty Quantification in Computational Sciences and Engineering, Rhode Island, 15.-17.06.2017)

MULTIDIMENSIONAL STOCHASTIC MATERIAL MODELING AT LARGE DEFORMATIONS CONSIDERING PARAMETER CORRELATIONS - Penner, Eduard; Caylak, Ismail; Mahnken, Rolf (Proceedings of the 2nd International Conference on Uncertainty Quantification in Computational Sciences and Engineering (UNCECOMP 2017))

(n)- AND (n + 1)-LAYERED COMPOSITE SPHERE MODELS FOR THERMO-CHEMO-MECHANICAL EFFECTIVE PROPERTIES - Mahnken, Rolf; Dammann, Christian; Lenz, Peter (International Journal for Multiscale Computational Engineering)

Thermo-chemo-mechanical Effective Properties for Homogeneous and Heterogeneous n -Phase Mixtures with Application to Curing - Dammann, Christian; Lenz, Peter; Mahnken, Rolf (Procedia CIRP)

Thermo-Mechanical Simulation of Hard Turning with Macroscopic Models - Uhlmann, E.; Mahnken, Rolf; Ivanov, I. M.; Cheng, C. (Lecture Notes in Production Engineering)

Effective meso properties for fibre reinforced polymer curing - Mahnken, Rolf

A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor - Mahnken, Rolf; Caylak, Ismail; Dridger, Alex (A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor)
This paper presents a numerical method for solution of a stochastic partial differential equation (SPDE) for a linear elastic body with stochastic coefficients (random variables and/or random fields). To this end the stochastic finite element method (SFEM) is employed, which uses W IENER’S polynomial chaos expansion in order to decompose the coefficients into deterministic and stochastic parts. As a special case, we consider isotropic material behavior with two fluctuating parameters. Computational approaches involving GALERKIN projection are applied to reduce the SPDE into a system of deterministic PDEs. Furthermore, we consider normally distributed random variables, which are assumed to be stochastically independent, and which establish the number of stochastic dimensions. Subsequently, the resulting finite element equation is solved iteratively. Finally, in a representative example for a plate with a ring hole we study the influence of different variances for material parameters on the variances for the finite element results.

Modeling of variant-interaction during bainitic phase transformation - Ehlenbröker, Ulrich; Mahnken, Rolf; Petersmann, M; Antretter, T (IOP Conference Series: Materials Science and Engineering)

Extension of a multi-mechanism model: Hardness-based flow and transformation induced plasticity for austenitization - Cheng, C.; Mahnken, Rolf (International Journal of Solids and Structures)

Macromodelling of Transformation Induced Plasticity combined with Viscoplasticity for Low-Alloy Steels - Schneidt, Andreas; Mahnken, Rolf (steel research international)

Determination of effective properties for CFRP curing coupled to viscoleasticity based on a three-scale framework - Dammann, Christian; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase field and diffusion models for lower bainite transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Two accuracy improvements on nonuniform transformation field analysis for plasticity coupled to softening - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase Ginzburg-Landau/Cahn-Hilliard systems for simulation of lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (Archive of Applied Mechanics)

A three-scale framework for fibre-reinforced-polymer curing part II: Mesoscopic modeling and macroscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

A three-scale framework for fibre-reinforced-polymer curing Part I: Microscopic modeling and mesoscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

An NTFA-based homogenization framework considering softening effects - Ju, X.; Mahnken, Rolf (Mechanics of Materials)

The concept of generalized stresses for computational manufacturing and beyond - Mahnken, Rolf; Cheng, Chun; Düsing, Martin; Ehlenbröker, Ulrich; Leismann, Thorben (GAMM-Mitteilungen)

PC expansion for material parameters using artificial data and statistical methods - Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

SFEM for rubber-like materials at large deformations - Penner, Eduard; Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

Lehrbuch der Technischen Mechanik - Band 1: Starrkörperstatik - Mahnken, Rolf

Mehrphasige ph ̈anomenologische sowie mehrskalige mikroskopische Modellierung von Phasenumwandlungen in einem Hybridumformprozess - Schneidt, Andreas

On the Design, Characterization and Simulation of Hybrid Metal-Composite Interfaces - Kießling, R.; Ihlemann, J.; Pohl, M.; Stommel, M.; Dammann, C.; Mahnken, Rolf; Bobbert, Mathias; Meschut, Gerson; Hirsch, F.; Kästner, M. (Applied Composite Materials)

Influences of interface and surface pretreatment on the mechanical properties of metal-CFRP hybrid structures manufactured by resin transfer moulding - Tröster, Thomas; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Bobbert, Mathias; Lauter, Christian; Zinn, Carolin; Wang, Zheng; Dammann, Christian (International Journal of Automotive Composites)

Intrinsische Herstellung hybrider Strukturkomponenten in einen modifizierte RTM-Prozess - Bobbert, Mathias; Dammann, C.; Wang, Z.; Zinn, C.; Mahnken, Rolf; Schaper, Mirko; Tröster, Thomas

Laserbehandlung intrinsisch gefertigter Hybride - strukturelle, mechanische und korrosive Eigenschaften - Zinn, C.; Bobbert, Mathias; Dammann, C.; Wang, Z.; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Tröster, Thomas

Influences of interface and surface pretreatment on the mechanical properties of metal-CFRP hybrid structures manufactured by resin transfer moulding - Tröster, Thomas; Schaper, Mirko; Meschut, Gerson; Mahnken, Rolf; Bobbert, Mathias; Lauter, Christian; Zinn, Carolin; Wang, Zheng; Dammann, Christian (International Journal of Automotive Composites)

A multi-mechanism model for cutting simulations based on the concept of generalized stresses - Cheng, C.; Mahnken, Rolf (Computational Materials Science)

Comparison of hyperelastic micromorphic, micropolar and microstrain continua - Leismann, T.; Mahnken, Rolf (International Journal of Non-Linear Mechanics)

MESOSCOPIC MODELING OF THE RTM PROCESS FOR HOMOGENIZATION - Mahnken, Rolf; Dammann, Christian

Dual-based adaptive FEM for inelastic problems with standard FE implementations - Widany, K.-U.; Mahnken, Rolf (International Journal for Numerical Methods in Engineering)

Adaptive FEM with goal-oriented error estimation and an approximation of the dual problem for inelastic problems - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Uncertainty quantification for linear elastic bodies with two fluctuating input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

A coupled phase-field - Cahn-Hilliard model for lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Transition from hyperelastic micromorphic to micropolar and microstrain continua - Leismann, Thorben; Mahnken, Rolf (PAMM)

Non-linear Stochastic Finite Element - Caylak, Ismail; Dridger, Alex; Mahnken, Rolf (PAMM)

Evaluation of different approaches for modeling phase transformations in machining simulation - Schulze, Volker; Uhlmann, Eckart; Mahnken, Rolf; Menzel, Andreas; Biermann, Dirk; Zabel, Andreas; Bollig, Patrick; Ivanov, Ivan M.; Cheng, Chun; Holtermann, Raphael; Bartel, Thorsten (Production Engineering)

A Novel Finite Element Approach to Modeling Hard Turning in Due Consideration of the Viscoplastic Asymmetry Effect - Uhlmann, Eckart; Mahnken, Rolf; Ivanov, Ivan Mitkov; Cheng, Chun (Procedia CIRP)

Simulation of lower bainitic transformation with the phase-field method considering carbide formation - Düsing, M.; Mahnken, Rolf (Computational Materials Science)

Parameter identification for rubber materials with artificial spatially distributed data - Nörenberg, Nicole; Mahnken, Rolf (Computational Mechanics)

Intrinsische Herstellung hybrider Strukturkomponenten in einem modifizierten RTM-Prozess - Bobbert, Mathias; Dammann, C.; Wang, Z.; Zinn, C.; Mahnken, Rolf; Meschut, Gerson; Schaper, Mirko; Tröster, Thomas

Eigenverstärkte Thermoplastverbunde - Verbundwerkstoffe (Teil 2) - Heim, Hans-Peter; Ries, Angela; Schöppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; Wünsch, Olaf; Al-Baldawi, Ammar; Rohde, Björn; Brückner-Foit, Angelika; et al. (Kunststoffe 104 (3/2014))
Anhand von Forschungsergebnissen aus dem Sonderforschungsbereich Transregio 30 wird dargestellt, wie Verbunde aus eigenverstärkten teilkristallinen oder hochgereckten amorphen Folien und Gewebe für Leichtbauanwendungen hergestellt und welche Eigenschaften erreicht werden können. Eine lokal differenzielle, thermo-mechanische Prozessführung ist sehr effizient variierbar, und somit lassen sich gradierte Eigenschaften im Sinne einer Funktionalisierung einstellen.

Self-Reinforced Thermoplastic Composites - Composite Materials (Part 2) - Heim, Hans-Peter; Ries, Angela; Schöppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; Wünsch, Olaf; Al-Baldawi, Ammar; Rohde, Björn; Brückner-Foit, Angelika; et al. (Kunststoffe international 104 (3/2014))
Anhand von Forschungsergebnissen aus dem Sonderforschungsbereich Transregio 30 wird dargestellt, wie Verbunde aus eigenverstärkten teilkristallinen oder hochgereckten amorphen Folien und Gewebe für Leichtbauanwendungen hergestellt und welche Eigenschaften erreicht werden können. Eine lokal differenzielle, thermo-mechanische Prozessführung ist sehr effizient variierbar, und somit lassen sich gradierte Eigenschaften im Sinne einer Funktionalisierung einstellen.

Self-Reinforced Thermoplastic Composites - Composite Materials (Part 1) - Heim, Hans-Peter; Ries, Angela; Schöppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; Wünsch, Olaf; Al-Baldawi, Ammar; Rohde, Björn; Brückner-Foit, Angelika; et al. (Kunststoffe international 104 (2/2014))
Mit eigenverstärkten Thermoplasten ist es möglich, Verbundsysteme herzustellen, die im Unterschied zu klassischen Faserverbundwerkstoffen keine Fremdfasern zur Verstärkung enthalten. Stattdessen werden thermoplastische Fasern oder Bändchen z.B. aus PP oder PE in einer identischen Matrix eingesetzt. Damit eröffnet sich ein hohes Leichtbaupotenzial bei gleichzeitig sehr guter Rezyklierbarkeit.

Eigenverstärkte Thermoplastverbunde - Verbundwerkstoffe (Teil 1) - Heim, Hans-Peter; Ries, Angela; Schöppner, Volker; Wibbeke, Andrea; Turek, Stefan; Damanik, Hogenrich; Mahnken, Rolf; Dammann, Christian; Wünsch, Olaf; Al-Baldawi, Ammar; Rohde, Björn; Brückner-Foit, Angelika; et al. (Kunststoffe 104 (2/2014))
Mit eigenverstärkten Thermoplasten ist es möglich, Verbundsysteme herzustellen, die im Unterschied zu klassischen Faserverbundwerkstoffen keine Fremdfasern zur Verstärkung enthalten. Stattdessen werden thermoplastische Fasern oder Bändchen z.B. aus PP oder PE in einer identischen Matrix eingesetzt. Damit eröffnet sich ein hohes Leichtbaupotenzial bei gleichzeitig sehr guter Rezyklierbarkeit.